Assessment of educational environment of midwifery students in Auxillary Nurse and Midwifery Institutes, Tamil Nadu - A descriptive study - Srinivas Govindarajulu; Geetha Rajasekar; Rakesh Anbazhagan; Thirumugam Muthuvel; B Subhavaishnavi; R Maanasa; Parameswari Srijayanth (Wolters Kluwer Medknow Publications, 2023)
Introduction: Tamil Nadu has a well-established public health-care delivery system with the Auxiliary Nurse and Midwifery (ANM) or Village Health Nurses. They learn and qualify for their job from ANM institutes and become the key field level functionary who interacts directly with the community. Their ability to provide quality community care is largely determined by the quality of ANM education they receive during their training. Hence, this study aimed to assess the perception of these students to facilitate a conducive educational environment. Methods: A descriptive study was carried out among 244 ANM students from across 10 randomly selected government ANM schools in Tamil Nadu. A self-administered Dundee Ready Educational Environment Measure (DREEM) questionnaire was used for assessment. The data was analyzed using EpiData. Results: Among the 244 students enrolled in the study, the mean (standard deviation) global DREEM score was 167.39 (±18.06). Student's academic perception was the highest (91%), followed by student's perception of atmosphere (84.2%), learning (84%), and teachers (83.5%), and the least average score was from student's social self-perception (74%). Conclusion: The study showed the nursing students' view on their academic learning environment as "more positive than negative," Centers were also considered excellent, and this assessment would provide an useful guide into the areas that students felt "good" about, which should be reinforced and the weaker areas that need to be strengthened for better services.